2004
DOI: 10.1111/j.1945-5100.2004.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and variability of the AIB amino acid in polar micrometeorites: Implications for the exogenous delivery of amino acids to the primitive Earth

Abstract: Abstract-Micrometeorites (MMs) are extraterrestrial particles ranging in size from 25 µm to 2 mm that survive atmospheric entry and are collected on the Earth's surface. They represent the largest mass flux (MF) of extraterrestrial material (30,000 ± 20,000 t/yr) to the present-day Earth. Studies of large collections of MMs suggest that about 20% have not been heated to high temperatures and that they contain organic carbon. Since non-protein amino acids have been found in some carbonaceous meteorites, they mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 57 publications
0
56
0
Order By: Relevance
“…The present-day amino acid flux on Earth was estimated to be around 3.0 × 10 7 kg yr −1 (Matrajt et al 2004) M s −1 of glycine. We may also mention the flux of organic carbon in IDPs of 3.6 × 10 10 kg yr −1 that survived re-entry on the early Earth proposed by Wilson (2009).…”
Section: Discussionmentioning
confidence: 99%
“…The present-day amino acid flux on Earth was estimated to be around 3.0 × 10 7 kg yr −1 (Matrajt et al 2004) M s −1 of glycine. We may also mention the flux of organic carbon in IDPs of 3.6 × 10 10 kg yr −1 that survived re-entry on the early Earth proposed by Wilson (2009).…”
Section: Discussionmentioning
confidence: 99%
“…That complex organic molecules are found in space and can successfully be delivered to Earth is well established. For example, amino acids have been found in meteorites (e.g., the Murchison meteorite, see Cronin, 1989) and Antarctic micrometeorites (Brinton et al, 1998;Matrajt et al, 2004), and polycyclic aromatic hydrocarbons have been found in some interplanetary dust particles (Clemett et al, 1993, or see Sandford, 2008, for a recent review). Large objects in space have also been shown to possess complex organic compounds; for example, dust from comet 81P/Wild 2 has been shown to contain a variety of organic materials (Brownlee et al, 2006;Keller et al, 2006;Sandford et al, 2006), including amino acids, such as glycine, and amines (Glavin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In a study searching for amino acids in Antarctic micrometeorites (Glavin et al 2004), the authors found no detectable levels of indigenous amino acids and concluded that these compounds are destroyed during atmospheric entry heating. However, Brinton et al (1998) and Matrajt et al (2004) found an amino acid, AIB (α-amino isobutyric acid), in some micrometeorites, suggesting that not all of the amino acids are destroyed during atmospheric entry.…”
Section: Introductionmentioning
confidence: 99%